Left Main Coronary Spasm: an Extremely Rare Entity with Possible Life-Threatening Complications - Al Emam, A.; Sricharoen, N. (International Journal of Angiology, 2016)
Coronary artery spasm is a known cause of acute coronary syndrome. However, left main coronary spasm is an extremely rare entity and can present in different ways depending on the duration and severity of the spasm. We present a 44-year-old female patient who presented with transient ST elevation in the lead aVR and ST depression in the lateral and inferior leads. Coronary angiography showed mid left main and ostial right coronary artery spasm that significantly improved after intracoronary nitroglycerine administration. Intravascular ultrasound showed no significant left main coronary atherosclerosis. She was treated chronically with calcium channel blockers (CCB), nitrates, and arginine with significant improvement. In conclusion, left main coronary spasm is an extremely rare entity with wide spectrum of clinical manifestations. Definite etiology is still questionable, and special precaution is needed during coronary angiography in order not to be confused with significant fixed lesions. Intravascular ultrasound can be valuable in excluding underlying atherosclerosis. Medical management with nitrates acutely then CCB is the mainstay of chronic management with PCI preserved to refractory cases.
Keywords: coronary intervention; left main coronary artery spasm; acute coronary syndrome; ischemia; cardiac catheterization; intravascular ultrasound